Corporate Social Responsibility, Inovasi, Green Investment Terhadap Pertumbuhan Penjualan - Citra Nidia Sari; Ovi Itsnaini Ulynnuha (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Sales growth is one of the indicators of a company's performance, as sales serve as a primary source of corporate revenue. Higher stability in sales generated by a company positively influences its sustainability. This study aims to analyze the effect of Corporate Social Responsibility (CSR), innovation, and Green Investment on sales growth in manufacturing companies in Indonesia. The research employs a quantitative method with multiple linear regression analysis. The sample consists of 119 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. The results reveal that CSR, innovation, and Green Investment significantly affect sales growth. The CSR and innovation variables exhibit a positive and significant impact, while Green Investment shows no effect and is not significant. These findings indicate that companies implementing CSR and innovation strategies can enhance sales growth.